Effects of microplastics on lentil (Lens culinaris) seed germination and seedling growth - De Silva, Y. Sanath K.; Rajagopalan, Uma Maheswari; Kadono, Hirofumi; Li, Danyang (Chemosphere (Oxford), 2022)
Widespread use of plastics and mishandling has resulted in severe environmental issues affecting seed germination and seedling growth. This study investigates the effect of polyethylene microplastics (740–4990 nm PEMPs) on lentil (Lens culinaris) seed germination and seedling growth using Biospeckle Optical Coherence Tomography (bOCT), a technique that we successfully demonstrated earlier in visualizing the internal activity of plants. Lentil seeds were exposed to PEMPs bioassay for seven days with 10, 50, and 100 mg L−1 concentrations. The average speckle contrast was calculated after 0 h, 6 h, 12 h, and 24 h of exposure, and statistically significant differences were observed just after 6 h of exposure under all the treatments. However, with conventional parameters, germination viability, germination rate, root and shoot lengths, fresh and dry seedling weights, and antioxidative enzymes, no significant effect was observed until 2 d of exposure. The results revealed that the presence of PEMPs significantly reduced the internal activity at the initial stages that could be visualized only by the use of bOCT, which has never been observed till now. Our results demonstrated for the first time the effect that microplastics indeed could hinder the internal activity during germination of the seeds, possibly resulting from the physical blockage of pores leading to stunted growth at later stages. [Display omitted] •The effect of polyethylene microplastics on lentil was investigated using Biospeckle Optical Coherence Tomography (bOCT).•bOCT is sensitive enough to observe the adverse effect of PEMPs on seed germination at an early stage before the germination.•A significant reduction of bOCT contrast was observed after 6 h for all PEMPs exposure, and the effect was dose-dependent.•Physical parameters and antioxidative enzymes were measured and compared with bOCT results.